Filantropi Islam dan Aktivitas Sosial Berbasis Masjid di Masjid Al-Hidayah Purwosari Yogyakarta - Muhammad Irham (Asosiasi Sosiologi Agama Indonesia (ASAGI), 2019)
This study explained how Mosque as the community of Muslim are able to finance social activities and conduct the program of community empowerment through the practice of Islamic philanthropy. By taking a case in a village in Sleman Regency, Yogyakarta, at where getting a Mosque that had been oriented toward religious and social activities of the community, namely the Mosque of Al-Hidayah Purwosari Sinduadi Village, Mlati District, which established since 1972 and has survived to the present. This research aimed to see how the Mosque's involvement in philanthropic activities led at the program of local community empowerment. This research is important in doing because of the mosque's ability to collect and manage the fund of philanthropic for social activities. The data of this study were obtained through step by step doing interview, observation, documentation and religious literature relevant to this study. The result of this study indicated thatthe fund of philanthropic came from zakat, infaq, alms and endowments that have been collected are distributed in the program of community empowerment which covered four main fields namely da'wah,education, social and economy. Finally, this study concluded that Mosque of al-Hidayah Purwosari was not only oriented toward worship, but also led to the programs of sustainable community empowerment throughthe practice of Islamic philanthropy.